Exploring The Essence of Web-Based Interactive Learning to Enhance Higher Order Thinking Skills in Nursing Students: A Focus Group Study: Web-based interactive learning for nursing education - Tambunan, Evelyn Hemme; Simbolon, Idauli; Rantung, Jeanny (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
This study aims to explore the essence of web-based interactive learning to enhance HOTS-analyzing, evaluating and creating in nursing students. This study implemented a qualitative research approach based on two focus group interviews on a sample of 20 resource participants including nursing students and faculty members from bachelor nursing program and information technology program at Universitas Advent Indonesia. All interviews were recorded, transcribed verbatim and analyzed for thematic contents using the standard to a consensus on thematic coding, the investigators finally convened to examine, classify, and arrange themes and categories. A thematic content analysis yielded three core themes: Gaps in Current Learning Methods, Potential Benefits of Web-Based Interactive Tools, Perceived Challenges. Categories were consented as variability in learning paces, engagement with teaching material, adaptability in learning approaches, feedback timeliness, interactive learning, resource and scalability limitations, enhanced flexibility, increased engagement through interactive features, personalized learning experiences, improved access to resources, support for collaborative learning, efficiency and scalability, technical issues, digital divide, reduced face-to-face interaction, equity and inclusivity, potential over-reliance on technology, privacy and security. This study highlights the multifaceted nature of the essence of web-based interactive learning to enhance higher order thinking nursing students. Implications are seen as valuable for enhancing higher order thinking skills to teaching, learning and academic support resources.